A line traversal approach to boundary detection on cadastral map - Su, Benjamin Chung Tai (Faculty of Computer Science and Information Technology, 2006)
This research considers the problem of cadastral map interpretation in Malaysian context and presents a parcel boundary detection model that supports creation of spatial database for cadastral maps. This model assumes the existence of some accurate algorithm to extract parcel comers from the raster image of cadastral map, such that the set of extracted corners can be used to further process the raster image to detect parcel boundaries.